Penggunaan Media Pembelajaran Berbasis Smartphone Dalam Mengatasi Kesulitan Belajar Siswa Pada Mata Pelajaran Aqidah Akhlak Siswa Kelas VIII MTs Tarbiyah Waladiyah Pulau Banyak - Ummi Atiah Lubis, Ahmad Fuadi, Nurmisda Ramayani (LPPPI Publishing, 2022)
The use of smartphones by teachers and students is done well and is very positive which can be used as a learning resource that provides a very broad scope so as to increase students' insight. Smartpones are used to help solve problems in learning aqidah morality. Efforts to overcome students' learning difficulties are carried out by utilizing a smartphone as a medium that helps each student's learning difficulties such as in overcoming different student learning abilities, improving students' memorization skills and instilling the character of Islamic teachings in students. by utilizing articles and videos as well as toutube related to the subject matter of the moral aqidah being taught. The use of smartphones can overcome student learning difficulties effectively because students are easier to understand the lessons of aqidah morals and make smartphones as the main learning resource because all materials can be accessed easily to get the required information related to the material discussed. Teachers can also use smartphones to facilitate the provision of learning information and assignments to students. The use of Smartphones in overcoming students' learning difficulties in the Aqidah Akhlak subject of class VIII MTs Tarbiyah Waladiyah Pulau Banyak has been done well. Smartphones can be used as learning resources for students to facilitate the teaching and learning process. Learning difficulties faced by students can be overcome properly by utilizing smartphones optimally and positively.